f(-1)=8f(0)=-3

Simple and best practice solution for f(-1)=8f(0)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(-1)=8f(0)=-3 equation:



f(-1)=8f(0)=-3
We move all terms to the left:
f(-1)-(8f(0))=0
determiningTheFunctionDomain f(-1)-8f0=0
We add all the numbers together, and all the variables
-8f+f(-1)=0
We multiply parentheses
-8f-1f=0
We add all the numbers together, and all the variables
-9f=0
f=0/-9
f=0

See similar equations:

| 22x–12=81 | | 2-2x/4=-12 | | 10x-16=x+164 | | Y/35x-7=49 | | 7p+4=169p | | 6x+29=77 | | -4x-9=-3x | | 20/n+5=9n= | | 69=6-7x | | (2x+2)(x+34)=180 | | 7d^2+3d-5=0 | | x^2+1=10x−8 | | 5/x+45=-10x | | 4|x|-10=10 | | O+87=87×n | | u/5+10=16 | | –10−9y=–4y+10 | | 5z+7=72 | | 4x/5x=6x+4/8x-15 | | -10(d+1)=-14. | | -8(t-95)=40 | | -10(d+1)=14. | | 6p-12=-24 | | 15−8=(12÷2h) | | –9r−5=–10r | | -8(t-95)=t | | –10+7d=2+3d | | 5(m+4)=70 | | 2=b-85/4 | | c−10=6c+10 | | 3t=4t+4 | | 8d=7d+5 |

Equations solver categories